Lesion mimic mutant 8 balances disease resistance and growth in rice - Zhao, Mengcan; Guo, Yunxia; Sun, Hang; Dai, Jichao; Peng, Ximan; Wu, Xuedong; Yun, Han; Zhang, Lisha; Qian, Yiming; Li, Xinying; He, Guanghua; Zhang, Changwei (Frontiers in Plant Science, 2023)
Lesion-mimic mutants (LMM) spontaneously produce necrotic spots, a process not affected by environmental stress or pathogen infection. In this study, we identified a LMM, lesion mimic mutant 8 (lmm8) in rice (Oryza sativa). The lmm8 mutant produces brown and off-white lesions on its leaves during the second- and third-leaf stages. The lesion mimic phenotype of the lmm8 mutant was enhanced by light. At the mature stage, lmm8 mutant are shorter and exhibit inferior agronomic traits than the wild type. Contents of photosynthetic pigments and chloroplast fluorescence were significantly reduced in lmm8 leaves, along with increased production of reactive oxygen species and programmed cell death compared to the wild type. The mutated gene was identified as LMM8 (LOC_Os01g18320) by map-based cloning. A point mutation occurred in LMM8, causing a Leu to Arg mutation of the 146th amino acid of LMM8. LMM8 encodes a protoporphyrin IX oxidase (PPOX) located in chloroplasts and involved in the biosynthesis of tetrapyrrole in chloroplasts. The lmm8 mutant showed enhanced resistance and broad-spectrum resistance. Together, our results demonstrate the importance of rice LMM8 protein in defense responses and plant growth in rice, and provides theoretical support for resistance breeding to improve rice yield.